2013
DOI: 10.1007/s00520-013-1899-z
|View full text |Cite
|
Sign up to set email alerts
|

Cancer pain management in an oncological ward in a comprehensive cancer center with an established palliative care unit

Abstract: Background This survey was performed to draw information on pain prevalence, intensity, and management from a sample of patients who were admitted to an oncologic center where a palliative care unit (PCU) has been established for 13 years. Methods Cross-sectional survey in an oncological department performed 1 day per month for six consecutive months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…Fifty-four (65%) patients were receiving inadequate cancer pain treatment with negative PMI which is higher than those reported by Apolone et al and Mercadante et al [4, 27]. However, a review article by Greco et al reported that inadequate cancer pain treatment can range from 8% to 82% [24].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Fifty-four (65%) patients were receiving inadequate cancer pain treatment with negative PMI which is higher than those reported by Apolone et al and Mercadante et al [4, 27]. However, a review article by Greco et al reported that inadequate cancer pain treatment can range from 8% to 82% [24].…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have examined undertreatment of cancer pain in different setup and populations [2, 4, 6, 1327]. The aim of this study was to look into the prevalence of inadequacy of cancer pain management and the subsequent pain interference with functioning of cancer patients visiting oncology ward of GUH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Pain management is often better in palliative care, but not all patients access this service. 26 Contextual integration outlines how the technology fits within the organisation where it will be implemented. Health professionals' apprehensions about the integration of PainCheck within current practice are reflected within this component.…”
Section: Discussionmentioning
confidence: 99%
“…An early identification of patients to be referred to a palliative care consultation is of paramount importance [3]. On the other hand, a positive cultural pressure of palliative care teams may positively influence the attitudes of oncologists in cancer pain management [4]. Authors report that 22 % of patients have a significant pain, that I assume to be >4, but overall, the mean intensity was quite low.…”
mentioning
confidence: 99%